Urban Expansion and Welfare Change in a Medium-sized Suburban City: Surakarta, Indonesia. (March 2020) - Buchori, Imam; Pangi, Pangi; Pramitasari, Angrenggani; Basuki, Yudi; Wahyu Sejati, Anang
This study observes the socio-spatial dynamics in the suburbs of a medium-sized city, particularly considering the extent to which shifting land use has influenced people's welfare. This case study selected suburban Surakarta, a medium-sized metropolitan city in Central Java Province, Indonesia. The methods employed were descriptive statistics and spatial analyses. Considering the data availability, unit of analysis was urban or rural villages ( kelurahan or desa ). The results show that the development follows the pattern of a regional network, but the spatial dynamics are quite different in each direction. Besides, the shift of land use from agriculture to urban land has not directly affected poverty reduction. In the study area, the increase in industrial land use showed a weak positive correlation with the addition of pre-prosperous families. On this basis, local governments should pay more attention to the existence of the native residents in developing suburbs so that they are not harmed by the shift in land use from agricultural to developed urban land.